Information Sources in Incident Journalism. Print Media Analysis - Rodríguez Carcela, Rosa María (2016)
This article is focused on the use of the news sources by Print Media in incident & crime reports. Official sources and agencies have a greater presence in analyzed newspapers. The Police is the major official and specialized source, and EFE Agency is the mostly quoted by journalists. The unofficial sources more often used by reporters are, in first place, the unidentified or confidential sources (commonly quoted generically as “according to consulted sources”) following the family and neighborhood sources. Graphic sources are becoming increasingly important in crime & incident reports and come mostly from photographers working for the newspapers and agencies. Reporters employ a large number of sources inadequately identified.